1605 m. Katekizmo aiškinamieji sakiniai - Judžentis, Artūras (Baltistica, 2010)
Complement clauses in the 1605 catechism The article deals with the complex sentences containing complement clauses in the 1605 Catechism. The anonymous translation of Ledesma’s shorter catechism was carefully compared with earlier Polish (anonymous) and Lithuanian (Daukša’s) translations, and with the corresponding sentences in Modern Lithuanian. Attention was paid to the syntactic structure of these sentences and to the relations between subordinators and the modal type of the complement clause, as well as between the main predicate and the complement clause. The conclusion is advanced that there were no semantically empty complementisers in the language of the catechism investigated. Instead, we find subordinators reflecting different types of clause modality: the complementisers jog and kad are used in declarative complement clauses, adunt (sporadically adant) and idant – in imperative clauses and gu, kas, kuris, kaip, kiek, kodrin in interrogative clauses. In that respect complement clauses in the 1605 Catechism differ from the corresponding clauses in Modern Lithuanian, where the same asemantic subordinator kad (and jog in non-standard language) is used both in declarative and imperative clauses. Furthermore, the semantic relationship between the modal type of complement clause and the main predicate is revealed. With verbs expressing epistemic modality the declarative or interrogative complement clauses are used. The imperative clauses are linked with the verbs, characterised by deontic and dynamic modality. The verbs of evaluative and equative semantics take declarative or imperative clauses. The number of complementisers in the 1605 Catechism is relatively large. It particularly applies to the functionally unmotivated usage of the complementisers jog and kad as well as adunt and idant. The usage of jog and kad could be explained as spreading of the latter from temporal subordinate clauses. But the usage of the complementisers adunt and idant still remains unexplained. Such variety of linking devices is common in translations made by more than one author, or in edited writings. In both cases more thorough investigation of the catechism and other old Lithuanian writings is needed.